Characterization of radiation damage to DNA by reaction with borohydride. - Schellenberg, K A (1981)
Irradiation of aqueous solutions of native calf thymus DNA with x-rays produced functional groups that reacted with sodium borohydride. The DNA was labeled with tritium from NaB3H4 to the extent of 2.0 x 10(-10) atom/dalton/rad. The presence of cysteamine or other radical scavengers, or saturation of the solution with nitrogen during irradiation decreased the labeling. After mild acid hydrolysis, the major tritium-containing moiety was identical with 2,3-dihydroxy-2-methylpropanoic acid in all chromatographic systems tested. The suggested mechanism of labeling involved reduction by borohydride of the potential aldehyde at carbon 6 of thymine glycol residues present in the irradiated DNA.